PRA PROSES PEMBUATAN E-KTP (Studi Kasus tentang Strategi Pelayanan Publik Bidang Informasi Kependudukan Dinas Kependudukan dan Pencatatan Sipil Kabupaten Kapuas Hulu) - Bls. P.Castro Yan Stur E.42009037 (FISIP Universitas Tanjungpura Pontianak, 2021)
The writing of this thesis intended to find out and analyze the problems according to writer’s first observation about the implementation of Electronic Identity Card program such as the mistaken of peoples data including in People Administration card, technical problems and geographics condition of Kapuas Hulu Regency. This study uses qualitative research methods perspective and use descriptive research.The conclusion of this study is the public service especially about the peoples data is not optimal so that makes a problem during data perfection and it cause a mistake in peoples data and invitation for the electronic identity card. Keywords: Pre-Process, Public Services, Electronic Identity Card.